O ensino de empreendedorismo no curso de graduação em Administração da Universidade Federal de Sergipe : A ótica de seus docentes - Souza, Ângela Maria de (2008)
The aim of this dissertation is to analyze the teaching process of entrepreneurship at Universidade Federal de Sergipe. It was investigated the challenges and the importance of this subject to professors at the Business Administration, considering the social representation to the entrepreneurship field, because there is not a consensus on theory. This case was focused on the titular professors and it was used a content analysis on the empiric survey, according to the methodology. The result revealed entrepreneurship has been teaching on the specific subject. Despite of this situation the entrepreneur behavior has been stimulated by some professors who are teaching the students how to deal with the uncertainty market. This effort has been done with no method because the professors don t know specific techniques on this area so that it has been the most relevant difficulty. Even considering its importance, the lack of structure and goal into entrepreneurship are also presented as the challenges on the course.